Male and female speech styles : Evidence from literary texts / Kamisah Ariffin and Sabariah Md. Rashid - Ariffin, Kamisah; Md. Rashid, Sabariah (Universiti Teknologi MARA Cawangan Pahang, 2001)
Numerous studies in conversational styles have claimed that men and women differ in their linguistic expressions. In addition, western behavioural constructs of masculinity and feminity are mirrorred in language where men's language is considered powerful while women's language is powerless. This paper reports the findings of a study on gender and speech style. The study involves text analysis. It seeks to examine the portrayal of the western perceptions of male and female Iinguistic expressions through the lexical and syntactic pragmatic traits of male and female speech in literary texts. Conversations of male and female characters as portrayed by the writers in an American novel, 'The Great Gatsby' and a Malaysian novel, 'Salina' were analysed. The analysis focuses on the use of special lexicon, imprecise intensifiers, super polite forms, expletives, tag questions, hedges and direct quotations by the characters in these two novels.